Islamic Education's Role in Building Character, Teaching Moral Values to Students, and Becoming the Pillar of a Quality Society - Rabe Alvi, Mohd; Yusron, Muhammad; Raza, Hamid (Yayasan Pendidikan Islam (YPI) AN NUR INSANI, 2024)
This study examines the extent to which strengthening Islamic education is able to shape individual character and humans as quality society union. Film Study: The strategy followed in this study is a form of reading referred as to film-reading (Documentary Form analysis). The findings of this study suggest that the enhancement of Islamic education can develop the characteristics one has as an individual. In good Islamic teachings, human beings are given moral values such as honesty, nose-to-tail and the pursuit of justice. Islamic education teaches and develops human character including empathy, tolerance from each other to collaborate. Also necessary, the ascendancy of Islamic education is one pillar to uphold a qualified society. If society was sound Islamic education then people of different faith and race will have peaceful life where in they can respect each other in every walk of their religious and cultural lives. Islamic education is also instrumental in shaping a high social conscious society that respects diversity and accepts the responsibility for all.